Katong gabii (That night) - Bolatag, Jeremy Luke 1996- (2018)
"Katong Gabii is a film that documents the lives of two survivors of the Roxas night market bombing in Davao City on September 2, 2016. It centers on Fatima, a vendor at the market whose intestines were shattered by a shrapnel, and Dennis, a truck driver whose wife and son died while getting a massage. The documentary follows these two survivors a year after the tragedy. The film examines the differences of the subjects' experiences - how they cope from the traumatic experience, how it is to be a Muslim and a Christian, and their social positions as a man and woman recovering from a life-altering incident. Katong Gabii highlights how strong Filipino faith is; it also emphasizes the alarming and terrifying effects of war on terror on innocent civilians, and that it does not choose its targets. The documentary uses the Cinema Verite style and it anchors on Psychoanalysis and Marxist Feminist theories to dissect the loss of Dennis, and the hardships of Fatima as a single mother in the lower working class."
Vita.
Thesis (A.B. Film)--University of the Philippines Diliman